Conceptualization of micromobility in Peru based on the application of kinetic energy thresholds - Iturraran Zapata, Rodrigo (2026)
Micromobility is an international concept within sustainable urban mobility that encompasses heterogeneous approaches and definitions depending on the regulatory and contextual framework, integrating both quantitative vehicle properties (physical and dynamic) and qualitative attributes (propulsion source, self-balancing capability, among others). In Peru, this concept has not been comprehensively developed within the national transport regulatory framework, revealing technical gaps related to importation and manufacturing control, vehicle characterization and homologation, as well as the definition of objective criteria for the management, regulation, and enforcement of non-motorized and personal mobility vehicles, particularly those exceeding the 25 km/h speed threshold. In this context, this article proposes a conceptualization of micromobility in Peru based on kinetic energy thresholds, estimated from mass and speed data corresponding to various vehicles available in the national market, including bicycles, scooters, motorized bicycles, motorcycles, motor scooters, and three-wheeled vehicles, as well as units associated with the pedestrian condition by extension. The analysis establishes a reference energy range between 1.2 and 10.4 kJ, which is contrasted with pedestrian–passenger car impact scenarios at speeds of 30, 20, 15, 10, and 5 km/h, used as a comparative risk framework.